Sentencing of Juvenile Narcotics Offenders in the Sidoarjo District Court - Rohi, Leba Max Nandoko; Tanudjaja, Tanudjaja (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research aims to answer the question of the judge's considerations in deciding a narcotics criminal case involving a child at the Sidoarjo District Court. And why is a form of legal protection provided to a child found guilty of committing a narcotics crime at the Sidoarjo District Court? This study is a legal research using a statute approach and a case approach. The analysis was carried out using qualitative juridical methods. The research found that the sentencing of a child in a narcotics case at the Sidoarjo District Court, based on Decision No. 12/Pid.Sus-Anak/2021/PN.Sda, considered the violation of Article 112 (1) of the Narcotics Law, the child’s confession, witness testimony, and evidence. The judge also took into account the child's age, emotional stress from parental divorce, and applied a restorative justice approach, opting for a six-month work training at Marsudi Putra Social Welfare Institution for rehabilitation, involving family, legal counsel, and the Probation Office.